ELECTROCHEMICAL BEHAVIOR OF POLYCRYSTALLINE COPPER DURING THE ADSORPTION OF CO ABSTRACT - J. Salimon; M. Kalaji (Universitas Gadjah Mada, 2003)
The electrochemical properties of electrode copper in carbon monoxide-saturated phosphate buffered solution were investigated. The electrochemistry of copper surface was sufficiently changed after the supporting electrolyte solution was saturated with CO. The hydrogen evolution region was depressed and shifted cathodically due to the adsorption process of CO on the copper surface in a linear or terminally bonded manner, Cu-CO . The oxidation and the reduction peaks of copper were significantly changed with two couple of redox peaks. This is due to the subsequent formation and the corresponding reduction of copper(I) and the copper carbon monoxides species. Further changed in electrochemical properties occurred when the electrode surface was polarized at high cathodic potential (-1.4 V) for a period of time (15 min). The hydrogen evolution region was further depressed due to the adsorption of CO process in multiple bonding sites as adsorbed bridge bonded CO, Cu-CO B L that occurred predominantly.